Is torso twist production the primary role of the torso muscles in front crawl swimming? - Andersen, J.; Sinclair, P.; Fernandes, R. J.; Vilas-Boas, J. P.; Sanders, R. (Sports Biomechanics, 2021)
The torso muscles play important roles in longitudinal rotation between the upper and lower torso on land but demands on these muscles at different swimming speeds and their role in torso twist in front crawl remains unclear. We aimed to compare torso muscle activity at different front crawl speeds and to assess the relationships between torso muscle activity and torso twist. Three-dimensional kinematics and torso muscle EMG data were collected from 15 male swimmers during middle-distance and sprint front crawl. Internal oblique, external oblique, and rectus abdominis, but not erector spinae, activities were greater at sprint than middle-distance pace. Sprint swimmers are likely to benefit from focusing training on the abdominal muscles. Cross-correlation peak coefficients between muscle activity and torso twist occurred with 517-775 and 400-600 ms lag at middle-distance and sprint paces (respectively). These lags are beyond the torso muscle electromechanical delay (~220 ms) and are too long for these muscles to produce movement changes. Further, peak coefficients coincided with both positive and negative shifts, indicating that muscle activity did not always precede kinematic changes. The torso muscles are therefore likely to play a greater role in maintaining stability and controlling posture in front crawl than producing torso twist.